Psicologia dos desastres: o cuidado de si de enfermeiros após uma situação de desastre - Brum, Lucas Motta (2016)
This study aimed to know the pratices of self care by nurses that have worked in Kiss nightclub disaster. Therefore, the research was developed through a qualitative and exploratory approach, and used individual interviews as a technique for data collection. We chose to study nurses who had worked in different places and in different ways in the disaster occurred in the city of Santa Maria - RS due to the fact that the researcher has participated as a volunteer in the care team to caregivers, where it had worked next to these professionals. The choice of participants was through a first contact with a professional who suggested other names in the "chain of informants," or as the methodology became known in Brazil - "snowball sampling". Thus, four nurses participate in the study. For data analysis, the content analysis technique was used, from Bardin. This study is divided into two articles, one of them focusing on the psychological intervention in disaster situations, given that this is the profession of researcher, and the second article sought to know self care practices used by nurses. The results presented in the first article emphasize the importance of psychology in disaster situations and the role of psychologists, together with other teams in situations like this, that increases the range of actions and care interventions to those involved. The results of the second article regarding the topic of self-care of each nurse, saw the importance of the relationship between the care team and how it reverberates in their lives and actions, focusing on the impossibility of dissociation between self care and care of others.